2022
DOI: 10.3389/froh.2021.794248
|View full text |Cite
|
Sign up to set email alerts
|

Deep Machine Learning for Oral Cancer: From Precise Diagnosis to Precision Medicine

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most prevalent cancers worldwide and its incidence is on the rise in many populations. The high incidence rate, late diagnosis, and improper treatment planning still form a significant concern. Diagnosis at an early-stage is important for better prognosis, treatment, and survival. Despite the recent improvement in the understanding of the molecular mechanisms, late diagnosis and approach toward precision medicine for OSCC patients remain a challenge. To enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…As is known, machine learning, an important component of AI algorithms, is aimed at generating an informed assessment by using numerical algorithms to detect relationships in information, which has the advantage of being able to computerize the hypothesis construction methods and, in some cases, optimize traditional statistical methods [7]. Machine learning possesses obvious advantages in mining and analyzing complex multimode big data, as well as potential clinical application value in constructing tumor-related risk models [8,9]. Therefore, the application of relevant AI algorithms to analyze multilevel and multiform data is playing an increasingly important role in tumor diagnosis and prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, machine learning, an important component of AI algorithms, is aimed at generating an informed assessment by using numerical algorithms to detect relationships in information, which has the advantage of being able to computerize the hypothesis construction methods and, in some cases, optimize traditional statistical methods [7]. Machine learning possesses obvious advantages in mining and analyzing complex multimode big data, as well as potential clinical application value in constructing tumor-related risk models [8,9]. Therefore, the application of relevant AI algorithms to analyze multilevel and multiform data is playing an increasingly important role in tumor diagnosis and prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of machine learning methods of data mining and artificial intelligence have been used for feature selection and classification in the diagnosis of diseases. Researchers have found that the use of modern techniques along with the main diagnosis and treatment templates can be far more practical and accurate [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], and [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore from our previous experience, machine learning algorithms have been applied to various fields in genomics (9), healthcare (10), computer vision (Malik et al 2021) etc. As the applications of these methods have assisted precision medicine scale, this would eventually bridge the gaps in oral squamous cell carcinoma (12). Ahmed et al have earlier investigated these methods from the AI dental imaging perspective.…”
Section: Introductionmentioning
confidence: 99%